Efektivitas Konseling Kelompok Teknik Self Management Untuk Meningkatkan Motivasi Belajar Pada Anak Binaan SMP di LPKA Kelas I Blitar - Ulfah Winda Anisa; Febranti Putri Navion (Guidance : Jurnal Bimbingan dan Konseling, 2022)
The aims of this study were (1) to determine the level of learning motivation of fostered children SMP in LPKA Class I Blitar (2) to determine the effectiveness of group counseling self management techniques in increasing learning motivation of fostered children SMP in LPKA Class I Blitar. This study uses a quantitative pre-experimental method with a one group pretest-posttest design. The population of this study is17 fostered children SMP in LPKA Class I Blitar with a total sample of 5 fostered children taken throught purposive sampling technique. The results showed that 12% of the target clildren’s learning motivation was in the high category, 59% in the medium category, and 29% in the low category. Based on the hypothesis test paired sample t test shows Sig. (2-tailed) 0,000 < 0,05 means that treatment is effective in increasing learning motivation of fostered children SMP in LPKA Class I Blitar. The n-gain score test showed an increase learning motivation in the medium category with a value of 0,45. With the increase in learning motivation, group counseling self management techniques is effective in increasing learning motivation for the fostered children SMP in LPKA Class I Blitar. Keywords: group counseling, self management techniques, learning motivation